The Level Of Community’s Sense Of Importance In Ownership Of Health Insurance - Nabila Erinaputri; Rhaina Al Yasin; Shifa Aulia Maghfiroh; Anisya Febriyanti (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Humans are expected to be able to manage risks, one of them is the risk of getting illness. One way to overcome the risk of getting sick is with health insurance. Health insurance developed in Indonesia is part of the national social security system which is administered using a compulsory social health insurance mechanism, Society does not need to pay high costs for health, and can be used for other needs. In writing scientific papers this time, research uses library research systematic review with a database search using Google Scholar. Papers selected to be used as the database for writing scientific papers are written in Indonesian and English, with a maximum issuance period of 5 years, complete, relevant text with the topic discussed, and an international standard serial number (ISSN). One of the Indonesian health insurance institutions, the Social Security Administrator in Indonesia (BPJS), wants to expand JKN membership throughout Indonesia. However, The level of a community’s sense of importance in ownership of health insurance depends on several factors, including age, education and knowledge, economic status, and social factors. There are various things that must be learned and understood from the importance of health insurance for the community through a program provided by the government, namely the National Health Insurance (JKN). The main benefit for the community is to have a sense of ownership of the program, to get health insurance in the form of health services both medically and non-medically.